Surface conductivity induced by fullerenes on diamond: passivation and thermal stability - Ristein, Jürgen; Ley, Lothar; et al. (Diamond and Related Materials, 2006)
The surface conductivity of hydrogen terminated diamond under atmospheric conditions is a well known phenomenon. Inspired by the surface transfer doping model [F. Maier, M. Riedel, B. Mantel, J. Ristein, L. Ley, Phys. Rev. Lett. 85, (2000) 3472] we have recently investigated thin C60 layers as an alternative to atmospheric adsorbates. We could indeed show that C60 induces a sub-surface accumulation layer that results in a surface conductivity comparable to the air induced one [P. Strobel, M. Riedel, J. Ristein, L. Ley, Nature 430, (2004) 439]. In the present work we investigate fluorinated fullerenes, namely C60F18, C60F36, and C60F48, as transfer dopants. The surface conductivity induced by fluorinated fullerenes increases with higher fluorination and achieves for C60F48 a level that exceeds that observed under atmospheric conditions by up to a factor of three. Furthermore, we study the thermal stability of the fullerene layers on diamond and their stabilisation by passivation with different dielectric films (SiO, CaF2, and Si3N4). In the case of fluorinated fullerenes we observe a significant improvement in thermal stability after passivation with dielectrics but the pristine conductivity level cannot be kept. A different kind of stabilisation is achieved for C60. After the simultaneous exposure to oxygen, light, and temperature of about 150 °C the surface conductivity induced by C60 is stable up to 350 °C in vacuum with an undiminished doping efficiency. We ascribe this effect to an oxygen mediated polymerisation of the C60 layer. © 2005 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2006.nat.dphy.IAP.exphys.surfac_6
Keywords: Fullerenes; p-type doping; Passivation; Thermal stability